2021
DOI: 10.1103/physreve.104.044802
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ion transport mediated by induced charge in ultrathin nanoporous membranes

Abstract: Ultrathin membranes with nanoporous conduits show promise for ionic separations and desalination applications, but the mechanisms underlying the nonlinear ionic transport observed in these systems are not well understood. Here, we demonstrate how induced charge at membrane interfaces can lead to nonlinear ionic transport and voltage-dependent conductance through such channels. The application of an electric field on a polarizable membrane leads to induced charges at the membrane interfaces. The induced charges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Figure 8. Under steady-state conditions, consequently, the large ionic flux of Cl – resulted in charge anisotropy, inducing a reverse electric potential across the active layer. , The induced electric field, conversely, accelerated the transport of monovalent cations (Li + , Na + , K + ) to preserve electroneutrality, coupling the two transport rates by electromigration, as illustrated in Figure C. This deduction corroborates with prior molecular dynamics simulations , and multi-ionic experiments. , However, the multivalent ions (Mg 2+ , Ca 2+ ) were inhibited by its lower partitioning rates, causing the ionic fluxes to be 1 order of magnitude lower than the monovalent ions.…”
Section: Resultssupporting
confidence: 81%
“…Figure 8. Under steady-state conditions, consequently, the large ionic flux of Cl – resulted in charge anisotropy, inducing a reverse electric potential across the active layer. , The induced electric field, conversely, accelerated the transport of monovalent cations (Li + , Na + , K + ) to preserve electroneutrality, coupling the two transport rates by electromigration, as illustrated in Figure C. This deduction corroborates with prior molecular dynamics simulations , and multi-ionic experiments. , However, the multivalent ions (Mg 2+ , Ca 2+ ) were inhibited by its lower partitioning rates, causing the ionic fluxes to be 1 order of magnitude lower than the monovalent ions.…”
Section: Resultssupporting
confidence: 81%
“…Induced charge due to membrane capacitance may partly explain the large apparent charge at large applied potentials (Δψ). 59 However, previous work found that induced charge on 55 nm thick silicon membranes is comparable to the surface charge of silica. 60 As the membrane capacitance and therefore the induced charge scales with the inverse of membrane thickness, we expect the (material specific) influence of induced charge to be minor in the 2 μm thick membranes used here.…”
Section: ■ Discussion Of the Large Surface Potentialmentioning
confidence: 93%
“…From the Gouy–Chapman equation we find that a pore with a surface potential between −0.21 and −0.28 V would contain approximately 15–60 times more charge than for a typical literature surface potential of −0.07 V. Such a large discrepancy cannot be explained by subtle experimental factors. Induced charge due to membrane capacitance may partly explain the large apparent charge at large applied potentials (Δψ) . However, previous work found that induced charge on 55 nm thick silicon membranes is comparable to the surface charge of silica .…”
Section: Discussion Of the Large Surface Potentialmentioning
confidence: 95%
“…The emergence of new membrane materials opens the possibility to surpass these limitations and achieve higher membrane permeance with better control of pore characteristics. For example, nanoporous atomically thin membranes (NATMs) made from graphene have been shown both experimentally and computationally to permit rapid solute diffusion while maintaining selectivity, with the selective layer being only 1-atom (< 0.4 nm) thick, and membrane fabrication using scalable methods has been demonstrated [ 4 , 7 , 8 , 19 , 20 , 12 ]. Single-layer graphene membranes can also withstand pressure differentials up to 100 bar if placed on the appropriate support structure, compared to typical transmembrane pressure (TMP) of < 300 mmHg (0.4 bar) [ 35 , 50 ].…”
Section: Introductionmentioning
confidence: 99%